2011
DOI: 10.5840/enviroethics20113314
|View full text |Cite
|
Sign up to set email alerts
|

Public Visions of the Human/Nature Relationship and their Implications for Environmental Ethics

Abstract: A social scientific survey on visions of human/nature relationships in western Europe shows that the public clearly distinguishes not only between anthropocentrism and ecocentrism, but also between two nonanthropocentric types of thought, which may be called "partnership with nature" and "participation in nature." In addition, the respondents distinguish a form of human/nature relationship that is allied to traditional stewardship but has a more ecocentric content, labeled here as "guardianship of nature." Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 4 publications
3
40
0
1
Order By: Relevance
“…Apparently, respondents in general do not clearly see differences between these positions. Previous quantitative research also showed similarities in the adherence to the partner with nature and participant in nature relationship (De Groot et al 2011;Ganzevoort and Van den Born, 2014;Verbrugge et al 2013). In qualitative research, however, respondents do distinguish between partner and participant positions (Van den Born 2008).…”
Section: Visions Of Naturementioning
confidence: 95%
“…Apparently, respondents in general do not clearly see differences between these positions. Previous quantitative research also showed similarities in the adherence to the partner with nature and participant in nature relationship (De Groot et al 2011;Ganzevoort and Van den Born, 2014;Verbrugge et al 2013). In qualitative research, however, respondents do distinguish between partner and participant positions (Van den Born 2008).…”
Section: Visions Of Naturementioning
confidence: 95%
“…In conservation morals include attitudes about right and wrong related to valued entities in nature. Assessing morals and analyzing their relationship with conservation-relevant behaviors may help predict reactions to policy alternatives (de Groot et al 2011;de Groot 2014). Better understanding and methodologically robust measurements of how morals affect behavior are needed to benefit HWC management and provide decision makers with additional tools for navigating tradeoffs in decision making (Vucetich & Nelson 2013;Sacchi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a previous study analysing the places where these same respondents located the greatest amount of landscape values [27], we found that cultural heritage played a very important role and that the percentage of respondents perceiving values connected to culture in their local landscape was slightly higher than those associated with nature (see García-Martín et al [27]). To us, this highlights the importance of landscape hermeneutics, which proposes that to ascribe meaning to cultural experiences this meaning has to be articulated [49,50]. There is a strong and commonly accepted narrative worldwide about the need to preserve nature and biodiversity from the threats that human action subjects them to-now heightened by the immediacy of climate change.…”
Section: A Shared Concern For the Environment And The Unarticulated Imentioning
confidence: 99%